Charged particles and neutral kaons in photoproduced jets at HERA - Breitweg, J; Derrick, M; Krakauer, D; Magill, S; Mikunas, D; Musgrave, B; Repond, J; Stanek, R; Talaga, R; Yoshida, R; Zhang, H; Mattingly, M; et al. (1998)
Charged particles (h±) and K0 mesons have been studied in photoproduced events containing at least one jet of ET > 8 GeV n a pseudorapidity interval (-0.5, 0.5) in the ZEUS laboratory frame. Distributions are presented in terms of transverse momentum, pseudorapidity and distance of the particle from the axis of a jet. The properties of h± within the jet are described well using the standard settings of PYTHIA, but the use of the multiparton interaction option improves the description outside the jets.